2022
DOI: 10.1096/fba.2021-00097
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic signaling in skin cancer

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Although the latter observation did not reach statistical significance, it is worth noting that the strongest signal of an enhanced response with combination ICI plus β-AR blockade was observed in a small subset (n = 19; 19%) of patients who were taking nonselective β-AR blockade compared to the majority (81%) of patients on a selective β-AR blocker, which further supports the previous observations regarding the importance of nonselective β-AR blockade (particularly targeting the β2-AR) as a means to fully optimize these therapeutically additive immunologic responses [92]. Several additional clinical trials utilizing nonselective β-AR blockade, with and without ICI, for patients with varying stages of melanoma are ongoing for which each trial's preliminary findings are highly anticipated [66].…”
Section: Impact Of ß-Adrenergic Immune Modulation In Melanoma: Clinic...supporting
confidence: 80%
See 2 more Smart Citations
“…Although the latter observation did not reach statistical significance, it is worth noting that the strongest signal of an enhanced response with combination ICI plus β-AR blockade was observed in a small subset (n = 19; 19%) of patients who were taking nonselective β-AR blockade compared to the majority (81%) of patients on a selective β-AR blocker, which further supports the previous observations regarding the importance of nonselective β-AR blockade (particularly targeting the β2-AR) as a means to fully optimize these therapeutically additive immunologic responses [92]. Several additional clinical trials utilizing nonselective β-AR blockade, with and without ICI, for patients with varying stages of melanoma are ongoing for which each trial's preliminary findings are highly anticipated [66].…”
Section: Impact Of ß-Adrenergic Immune Modulation In Melanoma: Clinic...supporting
confidence: 80%
“…Current clinical observations suggest that these pathways appear to be driven largely in part via expression of the β2-AR subtype, and increasing pre-clinical evidence suggests the β3-AR pathways may also be involved. Antagonism of β2-ARs has now exhibited repeated evidence of restoring anti-tumoral immunogenicity as well as enhancing effectiveness of ICI therapies within both pre-clinical and clinical melanoma models [28,66,71]. Our group's aforementioned multicenter phase II clinical trial observing the benefits of nonselective β-AR when combined with ICI (pembrolizumab) in patients with advanced melanoma is actively enrolling patients, and is expected to provide a more definitive answer regarding the clinical benefit of this combination in the setting of advanced melanoma [91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In skin cancers, especially in melanoma, all ß1, ß2, and ß3-ARs are expressed, of which ß1 appears to be the most significant. It is worth noting that among all tumor types studied, ß-ARs showed the highest expression in melanoma, which provided convincing evidence for the relationship between the adrenergic system and this skin cancer type [ 53 , 54 ].…”
Section: Review Of the Literaturementioning
confidence: 98%
“…This was linked to over-activation of the β2-adrenergic receptor (ADRB2)-cAMP-PKA pathway and increased angiogenesis in the stressed situation. There is now a large body of data from animals showing that adrenergic signaling is involved in tumor growth, metastasis, and overall mortality associated with multiple cancers, such as melanoma [ 17 ], colorectal cancer [ 141 ], breast cancer [ 222 ], and many more. In line with the rodent data, an early cohort study investigating over 10,000 women found significantly increased breast cancer risk in patients who had experienced a stressful life event, such as a divorce or death of a close family member [ 139 ].…”
Section: Adrenergic Signaling Linking Obesity and Cancermentioning
confidence: 99%